2023
DOI: 10.1021/acsnano.3c04328
|View full text |Cite
|
Sign up to set email alerts
|

Cascade and Ultrafast Artificial Antioxidases Alleviate Inflammation and Bone Resorption in Periodontitis

Abstract: Periodontitis, one of the most common, challenging, and rapidly expanding oral diseases, is an oxidative stress-related disease caused by excessive reactive oxygen species (ROS) production. Developing ROS-scavenging materials to regulate the periodontium microenvironments is essential for treating periodontitis. Here, we report on creating cobalt oxide-supported Ir (CoO–Ir) as a cascade and ultrafast artificial antioxidase to alleviate local tissue inflammation and bone resorption in periodontitis. It is demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…The positive control showed a large number of red nodules, indicating that calcium deposition was caused by osteogenic differentiation. The group treated with H 2 O 2 exhibited a reduced number of spots as a result of the suppression of ROS, which is consistent with previous reports . Meaningfully, this process was reversed in the H 2 O 2 +MT and H 2 O 2 +MT-CDs groups.…”
Section: Results and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The positive control showed a large number of red nodules, indicating that calcium deposition was caused by osteogenic differentiation. The group treated with H 2 O 2 exhibited a reduced number of spots as a result of the suppression of ROS, which is consistent with previous reports . Meaningfully, this process was reversed in the H 2 O 2 +MT and H 2 O 2 +MT-CDs groups.…”
Section: Results and Discussionsupporting
confidence: 91%
“…The alizarin red staining and its semiquantitative analysis further demonstrated that MT-CDs have a more significant advantage in promoting osteogenesis under ROS conditions than MT (Figure K). BMP-2 and Runx2 are essential for osteogenesis and accelerate the healing of bone defects. , BMP-2, a potent cytokine promoting predifferentiation of osteoblasts and bone development, plays a crucial osteogenic role . Additionally, Runx2 is an essential transcription factor that holds a pivotal function in the maturation of early stage osteoblasts .…”
Section: Results and Discussionmentioning
confidence: 99%
“…In addition, novel target-oriented characterisation techniques, especially in situ methods, such as in situ XAS, in situ XRD, and also in situ Raman, have emerged as frontier techniques to perform real-time monitors for a better understanding of the catalytic mechanisms, thus facilitating the DFT calculation, and guiding the future design of catalysts also deserves more attention to clearly detect the complex catalytic conversion chemistry and to reveal the catalytic mechanisms of RONBCs. 303–305…”
Section: Conclusion and Changing Statesmentioning
confidence: 99%
“…35–38 However, they often face challenges with interface integration, as poor integration can result in scaffold delamination and failure of tissue regeneration. 19,39,40…”
Section: Introductionmentioning
confidence: 99%